Pengembangan Media Pembelajaran IPA Berbasis Macromedia Flash 8 Materi Pencemaran Lingkungan untuk Siswa SMP Kelas VII - Fahmi Nasirudin; Lilik Mawartiningsih (Universitas Sebelas Maret, 2017)
The purposes of this research are to (1) To produce science learning media based Macromedia Flash 8 on the subject matter environmental pollution for students of grade VII junior high school, (2) To know the quality of science learning media based Macromedia Flash 8 on the subject matter environmental pollution can be used in science learning for student of grade VII junior high school. This research is development research (Research and Development) by using model of ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The research instrument is used a questionnaire.. The quality of instructional media is assessed by reviewers (1 media expert, 1 material expert, 1 science teacher, And response from 30 students of grade VII junior high school 5 Tuban through large and small group trial). The quality value data obtained was analyzed using qualitative and quantitative descriptive analysis based on the ideal assessment category. The result of the research based on criteria of validity according to (Khabibah 2006) can be concluded that Macromedia Flash 8 based learning media on environmental pollution material is included in the valid criteria, because the average total validation result from teacher, material expert, or media expert get more score than 4. Student response data on large group trials showed 86, 66%. Based on the criteria of positive responses of students according to (Khabibah 2006), it can be concluded that the response of students to media based learning Macromedia Flash 8 environmental pollution material is included in the category very positive, because more than 85% of students give a positive response. Based on the assessment of media experts, material experts, science subjects teachers and Student response reviewed from all aspects showed the quality of science learning media based Macromedia Flash 8 including excellent category . Based on the Assessment can be concluded that the science learning mediabased Macromedia Flash 8 on the subject matter of environmental pollution developed feasible use in science learning.